Below-the-Ankle Arrival Time as a Novel Limb Tissue Perfusion Index: Two-dimensional Perfusion Angiography Evaluation. (April 2020) - Ikeoka, Kuniyasu; Watanabe, Tetsuya; Shinoda, Yukinori; Minamisaka, Tomoko; Fukuoka, Hidetada; Inui, Hirooki; Ueno, Keisuke; Hoshida, Shiro
Purpose: To identify lower limb 2-dimensional (2D) perfusion angiographic parameters that are related to skin perfusion pressure (SPP), a predictor of wound healing in patients with chronic limb-threatening ischemia (CLTI) undergoing below-the-knee (BTK) endovascular treatment (EVT).Materials and Methods: Thirty-three consecutive patients (mean age 74.5 years; 18 men) with 47 isolated BTK lesions in 33 limbs (Rutherford category 3–5) underwent EVT. Dorsal and plantar SPPs were measured before EVT and the day after. The indexed blood flow below the ankle was measured using 2D perfusion angiography before and after EVT to determine changes in perfusion parameters [arrival time (AT), time to peak, wash-in rate, mean transit time, and width and area under the time-density curve] at rest vs during hyperemia induced with a 20-mg intra-arterial papaverine infusion. Correlations between the 2D perfusion parameters and SPPs were assessed using the Pearson coefficient. The cutoff points to predict mean SPPs >40 mm Hg were analyzed using a receiver operating characteristic curve; outcomes are reported as the area under the curve (AUC) with 95% confidence interval (CI).Results: After EVT at rest and during hyperemia, only AT was significantly changed, although hyperemia produced significant changes in all the pre-/post-EVT 2D perfusion parameters except the wash-in rate. Dorsal and plantar SPPs after EVT were significantly increased and correlated with hyperemic AT and the AT ratio (hyperemia/at rest values) below the ankle. Hyperemic ATs <6.3 seconds and AT ratios <0.78 were predictive factors for a mean SPP >40 mm Hg, with AUCs of 0.83 (95% CI 0.67 to 0.99) and 0.78 (95% CI 0.61 to 0.95), respectively.Conclusion: Hyperemic ATs <6.3 seconds or AT ratios <0.78 below the ankle may be essential to obtain sufficient SPPs for limb salvage in BTK lesions. Thus, the use of 2D perfusion angiography enabled the monitoring of lower limb tissue perfusion throughout EVT and may thereby optimize treatment of CLTI.